Airway wall thickness in patients with COPD and healthy current smokers and healthy non-smokers: Assessment with high resolution computed tomographic scanning - Deveci, F; Murat, A; Turgut, T; Altuntas, E; Muz, MH (Karger, 2004)
Background: Chronic obstructive pulmonary disease ( COPD) is characterized by airflow obstruction caused by emphysema or airway narrowing, or both. Recently airway dimensions have been measured using high-resolution computed tomography (HRCT). To evaluate large and small airway dimensions by HRCT and compare them with pulmonary function tests in patients with COPD and in smokers with or without airflow obstruction. Methods: We used HRCT scanning to measure airway wall thickness at the segmental and sub-segmental levels in COPD patients ( group II, stage II, n = 17, and group III, stage III, n = 5), healthy current smokers ( group I, n = 10) and healthy non-smokers ( group 0, n = 10). Results: FEV1 was lower in patients with severe or moderate COPD than in healthy current smokers and nonsmokers. FEV1 was lower in group I than group 0 ( p < 0.005). There was no statistically significant difference between patients with moderate COPD and severe COPD in the ratio of airway wall thickness to outer diameter (T/ D ratio) or the percentage wall area (WA%). Both groups II and III had higher T/D ratios than group I (p < 0.01), and group I had a higher T/ D ratio than group 0 (p < 0.001). Both groups II and III had higher WA% than group I ( p ! 0.01 and p < 0.05, respectively), and group I had a higher WA% than group 0 ( p < 0.001). A negative correlation was found between airway wall thickness and FEV1. Conclusions: Computed tomography measurements of large and small airway dimensions are useful for evaluating lung function in patients with COPD and healthy current smokers. Airway wall thickening is inversely related to the degree of airflow obstruction and positively related to cumulative smoking history. Copyright (C) 2004 S. Karger AG, Basel.
ERS 2002 Annual Congress -- 2002 -- Stockholm, SWEDEN
Keywords: chronic obstructive pulmonary disease; airway wall thickness; computed tomography, high-resolution; smoking